Roles of the Essential Protein FtsA in Cell Growth and Division in Streptococcus pneumoniae - Mura, Andrea; Fadda, Daniela; Perez, Amilcar J; Danforth, Madeline L; Musu, Daniela; Rico, Ana Isabel; Krupka, Marcin; Denapaite, Dalia; Tsui, Ho-Ching T; Winkler, Malcolm E; Branny, Pavel; Vicente, Miguel; et al. (Journal of bacteriology, 2017)
Streptococcus pneumoniae is an ovoid-shaped Gram-positive bacterium that grows by carrying out peripheral and septal peptidoglycan (PG) synthesis, analogous to model bacilli, such as Escherichia coli and Bacillus subtilis In the model bacilli, FtsZ and FtsA proteins assemble into a ring at midcell and are dedicated to septal PG synthesis but not peripheral PG synthesis; hence, inactivation of FtsZ or FtsA results in long filamentous cells unable to divide. Here, we demonstrate that FtsA and FtsZ colocalize at midcell in S. pneumoniae and that partial depletion of FtsA perturbs septum synthesis, resulting in elongated cells with multiple FtsZ rings that fail to complete septation. Unexpectedly, complete depletion of FtsA resulted in the delocalization of FtsZ rings and ultimately cell ballooning and lysis. In contrast, depletion or deletion of gpsB and sepF, which in B. subtilis are synthetically lethal with ftsA, resulted in enlarged and elongated cells with multiple FtsZ rings, with deletion of sepF mimicking partial depletion of FtsA. Notably, cell ballooning was not observed, consistent with later recruitment of these proteins to midcell after Z-ring assembly. The overproduction of FtsA stimulates septation and suppresses the cell division defects caused by the deletion of sepF and gpsB under some conditions, supporting the notion that FtsA shares overlapping functions with GpsB and SepF at later steps in the division process. Our results indicate that, in S. pneumoniae, both GpsB and SepF are involved in septal PG synthesis, whereas FtsA and FtsZ coordinate both peripheral and septal PG synthesis and are codependent for localization at midcell.IMPORTANCEStreptococcus pneumoniae (pneumococcus) is a clinically important human pathogen for which more therapies against unexploited essential targets, like cell growth and division proteins, are needed. Pneumococcus is an ovoid-shaped Gram-positive bacterium with cell growth and division properties that have important distinctions from those of rod-shaped bacteria. Gaining insights into these processes can thus provide valuable information to develop novel antimicrobials. Whereas rods use distinctly localized protein machines at different cellular locations to synthesize peripheral and septal peptidoglycans, we present evidence that S. pneumoniae organizes these two machines at a single location in the middle of dividing cells. Here, we focus on the properties of the actin-like protein FtsA as an essential orchestrator of peripheral and septal growth in this bacterium.
Keywords: Streptococcus pneumoniae; FtsA; cell division; Gram-positive cocci